Biotechnological tools to improve bioremediation of phenol by Acinetobacter sp. RTE1.4 - Paisio, Cintia Elizabeth (2016)
The use of native bacteria is a useful strategy to decontaminate industrial effluents as well as the environment. Acinetobacter sp. RTE1.4 was previously isolated from polluted environments and constitutes a promising alternative for this purpose due to its capability to remove phenol from synthetic solutions and industrial effluents. In this work, this strain was identified at species level as A. tandoii RTE1.4. Phenol degradation pathway was studied and some reaction intermediates were detected, confirming that this strain degraded phenol through ortho-cleavage of the aromatic ring. Phenol removal assays were carried out in a stirred tank bioreactor and a complete degradation of the contaminant was achieved after only 7 h, at an aeration rate of 3 vvm and at agitation of 600 rpm. Moreover, this bacterium was immobilized into calcium alginate beads and an increase in phenol biodegradation with respect to free cells was observed. The immobilized cells were reused for four consecutive cycles and stored at 4°C for 9 months, during which phenol removal efficiency was maintained. Post-removal solutions were evaluated by Microtox® test, showing a toxicity reduction after bacterial treatment. These findings demonstrated that A. tandoii RTE1.4 might be considered as a useful biotechnological tool for an efficient treatment of different solutions contaminated with phenol in bioreactors, using either free or immobilized cells.